Weaning from long term continuous positive airway pressure or noninvasive ventilation in children. Issue 10 (17th July 2017) - Mastouri, Meriem; Amaddeo, Alessandro; Griffon, Lucie; Frapin, Annick; Touil, Samira; Ramirez, Adriana; Khirani, Sonia; Fauroux, Brigitte
Abstract: Objectives: A significant number of children are able to discontinue long term continuous positive airway pressure (CPAP) or noninvasive ventilation (NIV) but the underlying disorders, weaning criteria, and outcome of these children have not been studied. Study design: Retrospective cohort follow up. Subject selection: Consecutive children who were weaned from long term CPAP/NIV between October 2013 and January 2016. Methodology: Underlying disorders, weaning criteria, and clinical outcome were analyzed. Results: Fifty eight (27%) of the 213 patients on long term CPAP/NIV could be weaned from CPAP/NIV with 50 patients being weaned from CPAP and 8 from NIV. Most patients were young children with upper airway anomalies, Prader Willi syndrome or bronchopulmonary dysplasia. CPAP/NIV was discontinued following spontaneous improvement of sleep‐disordered breathing in 33 (57%) patients, upper airway surgery ( n  = 14, 24%), maxillofacial surgery ( n  = 6, 11%), neurosurgery ( n  = 1, 2%), upper airway and neurosurgery ( n  = 2, 3%), or switch to oxygen therapy ( n  = 2, 3%). CPAP/NIV was discontinued due to normal nocturnal gas exchange during spontaneous breathing in all patients, with an obstructive apnea‐hypopnea index ≤6 events/h on a combined poly(somno)graphy in 27 patients. A relapse of obstructive sleep apnea was observed after a median delay of 2 years in six patients who resumed CPAP and in one patient who underwent midface distraction. Conclusions: Weaning from CPAP/NIV is possible in children treated with long term CPAP/NIV but is highly dependent on the underlying disorder. Spontaneous improvement is possible but most children need specific surgery. Long term follow‐up is necessary in children with underlying disorders.